Modeling a suspension for a calibrator of interferometric gravitational wave detector using finite elements method - Frajuca, Carlos; Prado, Andre Cardoso Do; Bortoli, Fabio Da Silva; Souza, Renato Chaves; Duarte, Roberto Nunes; Magalhaes, Nadja Simao (AIP conference proceedings, 2023)
Interferometric gravitational wave detectors (IGWD) are very complex detectors, the need for locking the detector in a dark fringe condition besides the vibrations that affect the mirrors is very difficult challenge, creating the need for active suspension systems. These active systems make the system reach the desired sensitivity but make the calibration of such detectors much more difficult. To solve this problem a calibrator is proposed, a resonant mass gravitational wave detector could be used to detect the same signal in a narrower band and use the measured amplitude to calibrate the IGWD, as resonant mass gravitational wave detectors are easily calibrated. The main challenge in this design is the operational frequency of the calibrator, these massive detectors usually were built in frequencies close to 1 kHz but the frequency of the Gravitational Waves detected is around 100 Hz, then the design should adapt to this. This work aims to design and simulate a suspension of the mechanical antenna of such a calibrator. The suspension is modelled in finite elements method and a design of such a suspension is presented as its normal vibration modes.